1982
DOI: 10.1901/jaba.1982.15-431
|View full text |Cite
|
Sign up to set email alerts
|

The Token Economy: A Decade Later

Abstract: In the last decade, the token economy has been extended widely across populations and behaviors in treatment, rehabilitation, educational, and community settings. Outcome research has expanded as well to include large-scale program evaluations and comparative and combined treatment studies of the token economy. In a previous review (Kazdin & Bootzin, 1972), several obstacles were identified for the effective application of the token economy. These included identifying procedures to enhance program efficacy, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
11

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(128 citation statements)
references
References 63 publications
2
115
0
11
Order By: Relevance
“…Further studies have used tokens, points and star charts as the predictive stimuli (Kazdin, 1982). In these cases the stimuli that predict reinforcement at the end of the delay may serve as conditioned reinforcers through multiple pairings with the delayed reinforcers.…”
Section: Using a Time Timer Tm To Increase Appropriate Waiting Behavimentioning
confidence: 99%
“…Further studies have used tokens, points and star charts as the predictive stimuli (Kazdin, 1982). In these cases the stimuli that predict reinforcement at the end of the delay may serve as conditioned reinforcers through multiple pairings with the delayed reinforcers.…”
Section: Using a Time Timer Tm To Increase Appropriate Waiting Behavimentioning
confidence: 99%
“…Levando isto em linha de conta, supõe-se que o sistema de economia de fichas foi eficaz na melhoria da motivação dos alunos, o que vai de encontro ao descrito na literatura, nomeadamente, que este tipo de procedimento é eficaz no aumento da motivação dos alunos (Kazdin, 1982;e Martin & Pear, 2009 …”
Section: Discussionunclassified
“…Deste modo, seja qual for o programa de treino deverá ser constituído pelos seguintes aspetos: objetivo geral, objetivos específicos, definição do comportamento-alvo, definição do repertório de entrada, ou seja, dos pré-requisitos, fases, procedimentos, materiais, local do treino, formas de registo, processos de avaliação e ainda a especificação dos aspetos motivacionais (Galindo, 2015).A par disto, os aspetos motivacionais também são de extrema importância, já que têm um papel muito importante no sucesso do programa de treino, sendo por isso fundamental recorrer à aplicação de um sistema de economia de fichas para melhorar a motivação dos alunos alvo de intervenção. (Kazdin, 1982;Martin & Pear, 2009). Galindo (2015) aplicou estes programas a crianças com problemas de insucesso escolar nos primeiros três anos do ensino básico; observou que todos os alunos acompanhados progrediram e adquiriram os repertórios ensinados, independentemente da causa do problema, da idade, do tempo de treino ou da competência treinada.…”
Section: Introductionunclassified
“…The stimuli will serve as most effective conditioned reinforcers if they are regularly presented contingent upon the target response and if they reliably predict reinforcement. Considerable research has identified the effectiveness of tokens, points, gold stars, and the like in achieving this purpose (Kazdin, 1982;Kazdin & Bootzin, 1972), yet the identification of less contrived, more naturally occurring conditioned reinforcers will be useful for ensuring generalization to other settings. Pictures of a desired object, edible item, or activity may serve a similarly useful purpose when presented during a delay, particularly if the pictures are being used concomitantly in a communication teaching program (e.g., Bondy & Frost, 1993).…”
Section: Basic Research Related To Delayed Reinforcementmentioning
confidence: 99%
“…As an example of such a chain, consider a teaching situation in which a child (a) accumulates pennies for each correct response, (b) exchanges the pennies for tokens after a specified number of pennies are accumulated, then (c) exchanges the tokens for a desired activity after a specified number of tokens are accumulated. As previously noted, the use of tokens as conditioned reinforcers in applied settings has been elaborated upon a great deal (e.g., Kazdin, 1982;Kazdin & Bootzin, 1972), but how the availability of chains of conditioned reinforcers systematically affects choice making in practical situations is currently unknown. In addition, the identification of more naturally occurring stimulus chains will again be profitable.…”
Section: Basic Research Related To Delayed Reinforcementmentioning
confidence: 99%